2017
DOI: 10.1089/ten.tea.2017.0069
|View full text |Cite
|
Sign up to set email alerts
|

Renal Regenerative Potential of Different Extracellular Vesicle Populations Derived from Bone Marrow Mesenchymal Stromal Cells

Abstract: Extracellular vesicles (EVs) derived from human bone marrow mesenchymal stromal cells (MSCs) promote the regeneration of kidneys in different animal models of acute kidney injury (AKI) in a manner comparable with the cells of origin. However, due to the heterogeneity observed in the EVs isolated from MSCs, it is unclear which population is responsible for the proregenerative effects. We therefore evaluated the effect of various EV populations separated by differential ultracentrifugation (10K population enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
163
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 47 publications
(57 reference statements)
9
163
0
Order By: Relevance
“…As described, sEVs seem to exert most therapeutic functions of MSCs [16,56]. However, in other cell systems larger vesicles have been found to also mediate functional activities [57].…”
Section: Discussionmentioning
confidence: 99%
“…As described, sEVs seem to exert most therapeutic functions of MSCs [16,56]. However, in other cell systems larger vesicles have been found to also mediate functional activities [57].…”
Section: Discussionmentioning
confidence: 99%
“…STEC-HUS Shiga toxin-producing Escherichia coli -hemolytic uremic syndrome, aHUS atypical HUS, TTP thrombotic thrombocytopenic purpura, VWF von Willebrand factor, CD62E E-selectin, ICAM-1 intercellular adhesion molecule 1, NDI nephrogenic diabetes insipidus (DI), CDI central DI, ADPKD autosomal dominant polycystic kidney disease, ATG antithymocyte globulin, SLE systemic lupus erythematosus, APS anti-phospholipid syndrome, A adipocytes, I islet cells a Detected extracellular vesicles were not specified as exosomes, microvesicles or apoptotic bodies b Elevated extracellular vesicles and miRNA may serve as biomarkers c The exosomal fraction is responsible for the regenerative effects [146] d Na/H exchanger isoform 3, fetuin-A or activating transcription factor 3 may reflect tubular injury e miRNA profiles correlated with perturbed renal function and renal fibrosis f Indicating complement activation g Correspond to the Birmingham vasculitis activity score h A miRNA profile derived from miRNA containing microvesicles. Protein biomarkers include α1-antitrypsin, aminopeptidase N, vasorin precursor, ceruloplasmin, and podocalyxin…”
Section: Extracellular Vesicles As Biomarkers and Promoters Of Kidneymentioning
confidence: 99%
“…For example, EVs derived from marrow or adipose MSCs affect the phenotype and induce healing of many different tissue and cell types, including liver (51), heart (52), pulmonary epithelial cells and kidney (53,54) as well as promote angiogenesis (55,56). Consistent with these regenerative capacities of stem cell EVs, a recent study demonstrated that implantation of healthy hypothalamic stem/progenitor cells into the hypothalamus leads to the slowing of ageing (57).…”
Section: Evsmentioning
confidence: 99%